Exogenous application of Eucommia ulmoides β-1, 4-glucanase promotes propagation by increasing the expression of wound healing genes - Jinyu Yang; Runying Wang; Na Ren; De-gang Zhao; Xiaozhen Huang; Yichen Zhao (Scientific Reports)
Abstract Eucommia ulmoides (E. ulmoides) is a valuable gum-producing plant and traditional Chinese medicine. The utilization value of E. ulmoides varies according to the sex of the plant, and due to its perennial characteristics, the identification of male and female is challenging. To meet production demands, gender selection through grafting has been employed. The fusion of rootstock and scion cells in grafted plants can be enhanced by β-1, 4-glucanase, thus improving the grafting survival rate. However, extracting β-1, 4-glucanase in vivo poses difficulties. In this study, the β-1, 4-glucanase gene of E. ulmoides was cloned, and the total length of the gene was 1917 bp, encoding 638 amino acids. Pichia pastoris engineering bacteria were used to express β-1, 4-glucanase. The optimal fermentation conditions included a pH of 6, a temperature of 28 ℃, a methanol content of 1.5%, and a fermentation period of 96 hours. After purification, the enzyme activity of the target protein was measured to be 286.35 U/mL. Protein concentrations of 5 mg/mL, 10 mg/mL, and 15 mg/mL were tested for E. ulmoides grafting. The results showed that the protein could promote wound healing and improve the survival rate of E. ulmoides grafting. In conclusion, this study successfully developed an enzyme that improves the survival rate of E. ulmoides grafting, and provides valuable insights for the breeding of male and female E. ulmoides grafts.